Wolbachiainfections inAedes aegyptidiffer markedly in their response to cyclical heat stress - Perran A. Ross; Itsanun Wiwatanaratanabutr; Jason K. Axford; Vanessa L. White; Nancy M. Endersby-Harshman; Ary A. Hoffmann (My University, 2016)
Abstract Aedes aegypti mosquitoes infected with Wolbachia bacteria are currently being released for arbovirus suppression around the world. Their potential to invade populations and persist will depend on interactions with environmental conditions, particularly as larvae are often exposed to fluctuating and extreme temperatures in the field. We reared Ae. aegypti larvae infected with different types of Wolbachia ( w Mel, w AlbB and w MelPop) under diurnal cyclical temperatures. Rearing w Mel and w MelPop-infected larvae at 26-37°C reduced the expression of cytoplasmic incompatibility, a reproductive manipulation induced by Wolbachia . We also observed a sharp reduction in the density of Wolbachia in adults. Furthermore, exposure to 26-37°C over two generations eliminated both the w Mel and w MelPop infections. In contrast, the w AlbB infection was maintained at a high density, exhibited complete cytoplasmic incompatibility, and was transmitted from mother to offspring with a high fidelity under this temperature cycle. These findings have implications for the success of Wolbachia interventions across different environments and highlight the importance of temperature control in rearing.
Keywords: Cytoplasmic incompatibility; Insect symbiosis and bacterial influences